A Novel Organic–Inorganic-Nanocomposite-Based Reduced Graphene Oxide as an Efficient Nanosensor for NO2 Detection - Masoud Khaleghiabbasabadi; Hadi Taghavian; Pooya Gholami; Saeed Khodabakhshi; Mohammad Gheibi; Stanisław Wacławek; Miroslav Černík; Daniele Silvestri; Klaudia Barbara Raczak; Reza Moezzi (Nanomaterials)
There are three components to every environmental protection system: monitoring, estimation, and control. One of the main toxic gases with considerable effects on human health is NO2, which is released into the atmosphere by industrial activities and the transportation network. In the present research, a NO2 sensor is designed based on Fe3O4 piperidine-4-sulfonic acid grafted onto a reduced graphene oxide Fe3O4@rGO-N-(piperidine-4-SO3H) nanocomposite, due to the highly efficient detection of pollution in the air. In the first phase of the present study, the nanocomposite synthesis is performed in four steps. Afterward, the novel fabricated nanosensor is characterized through energy dispersive X-ray spectroscopy (EDX), Fourier transform infrared spectroscopy (FTIR), thermogravimetric analysis (TGA), Raman, surface area analysis, and field emission scanning electron microscopy (FE-SEM). To determine the optimal condition for sensor performance, graphene-based nanosensors are prepared with various weight percentages (wt%) of rGO-N-(piperidine-4-SO3H) (1 wt%, 5 wt%, 10 wt%, and 15 wt%). During the experimental process, the performance of the sensors, in terms of the sensitivity and response time, is investigated at different NO2 concentrations, between 2.5 and 50 ppm. The outputs of this study demonstrate that the synthesized nanosensor has the best efficiency at more than a 5 ppm contamination concentration and with at least 15 wt% of rGO-N-(piperidine-4-SO3H).